THE INFLUENCE OF ORGANIZATIONAL CULTURE, MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. PRIMA KARYA SUKSES- TANGERANG - Kurniawati, Diana (International Research of Multidisciplinary Analysis, 2024)
The success of an organization including PT Prima Karya Sukses-Tangerang is influenced by employee performance (job performance). Therefore, performance is determined among others by organizational culture, motivation and perceived job satisfaction. So automatically employees will always show good performance and make a good contribution to the organization. The purpose of this study was to determine how much influence the variables of Organizational Culture, Motivation and Job Satisfaction on Employee Performance at PT. Prima Karya Sukses Tangerang. The method used is the quantitative method and analyzes the effect of the independent variable on the dependent variable, the measuring method used is a Likert scale by taking 35 respondents from the existing population as research respondents / census methods. Multiple Linear Regression Analysis using statistical analysis with the SPSS 20 program. From the research, it is known that organizational culture partially has no and insignificant effect on employee performance, while motivation and job satisfaction partially have a positive and significant effect on employee performance. The Ftest test shows that organizational culture, motivation and job satisfaction simultaneously affect employee performance